ChemInform Abstract: Dibenzo[a, c]carbazoles from 2‐(2‐Bromoaryl)‐3‐arylindoles via a Palladium‐Catalyzed Intramolecular C—H Functionalization/C—C Bond Formation Process. Issue 19 (18th April 2013) - Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia
Abstract The present reaction provides a new versatile approach to dibenzo[a, c]‐carbazoles tolerating a variety of useful substituents.